Ukraine : Technical Assistance Report-Public Investment Management Assessment. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report on Ukraine highlights that Ukraine currently has an efficiency gap of around 32 percent, which ranks it below average amongst emerging market countries and other comparators. Persistent under-investment, the currently high stock of debt, and ongoing institutional weaknesses, coupled with effects of the conflict in the East could see this gap continuing to grow, absent concerted efforts to reverse recent trends. The report also analyses that government policy on fiscal decentralization, articulated in the government's 2014 coalition agreement, has the potential to significantly impact on the allocation of public investment. The institutional framework is weak in all areas. It is in terms of effectiveness of the institutions that the Ukrainian public investment management system really falls short. Twelve institutions are ranked as ineffective while a further two are moderately effective, with only one institution scoring a high rank in this category. While the picture looks bleak, some recent initiatives may bring about significant improvements.